2016
DOI: 10.1159/000445251
|View full text |Cite
|
Sign up to set email alerts
|

Cytochrome P450 17A1 Inhibitor Abiraterone Acetate Counteracts the Heat Shock Protein 27's Cell Survival Properties in Prostate Cancer Cells

Abstract: Introduction: Inhibition of androgen synthesis by abiraterone acetate (AA) entails enhanced overall survival rates and clinical benefit for patients with locally advanced and metastasized prostate cancer (PC). The expression of heat shock protein 27 (HSP27) is generally associated with cytoprotection and was demonstrated to mediate chemoresistance under cytostatic therapy, for instance, docetaxel treatment. In this study, we investigated the impact of AA treatment on HSP27 expression and PC cell growth. Materi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
1
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 25 publications
(34 reference statements)
2
1
0
Order By: Relevance
“…In the present study, we have demonstrated that enzalutamide attenuates the proliferation of PC cells in a time‐ and dose‐dependent manner, demonstrating different drug sensitivities of the cell lines. These data are supported by previous studies using a similar experimental approach, such as PC cell growth inhibition by abiraterone, in vitro treatment of PC with enzalutamide, and mouse xenograft models …”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…In the present study, we have demonstrated that enzalutamide attenuates the proliferation of PC cells in a time‐ and dose‐dependent manner, demonstrating different drug sensitivities of the cell lines. These data are supported by previous studies using a similar experimental approach, such as PC cell growth inhibition by abiraterone, in vitro treatment of PC with enzalutamide, and mouse xenograft models …”
Section: Discussionsupporting
confidence: 87%
“…In the present study, we have demonstrated that enzalutamide attenuates the proliferation of PC cells in a time-and dose-dependent manner, demonstrating different drug sensitivities of the cell lines. These data are supported by previous studies using a similar experimental approach, such as PC cell growth inhibition by abiraterone, [27][28][29][30] in vitro treatment of PC with enzalutamide, and mouse xenograft models. 7,[31][32][33] Growth-inhibitory effects during anticancer therapy has been shown to be often accompanied by an increase of p53 protein, which acts in surveillance of genomic integrity and oncogene activity.…”
Section: Discussionsupporting
confidence: 86%
“…Furthermore, abiraterone inhibits CYP21A2 30 and CYP11B1 9 which in the clinical setting, forces co-administration of prednisone to mitigate the resulting mineralocorticoid excess 30 . Besides the effects from the binding of abiraterone to CYP enzymes, it may have several other anticancer effects, involving binding to the androgen receptor, 3β‐hydroxysteroid dehydrogenase inhibition as well as decreasing the levels of heat shock protein 27, a cytoprotective agent involved in drug resistance issues, in androgen-insensitive prostate cancer cells 31 . Although these types of effects may be favourable, a selectively binding compound could reduce the risk of adverse side effects and can additionally be used as pharmacological tools in prostate cancer research.…”
Section: Discussionmentioning
confidence: 99%